Research Through, With and As Storying - Phillips, Louise Gwenneth (Taylor & Francis, 2018)
Research Through, With and As Storying explores how Indigenous and non-Indigenous scholars can engage with storying as a tool that disassembles conventions of research. The authors explore the concept of storying across different cultures, times and places, and discuss principles of storying and storying research, considering Indigenous, feminist and critical theory standpoints. Through the book, Phillips and Bunda provide an invitation to locate storying as a valuable ontological, epistemological and methodological contribution to the academy across disciplines, arguing that storying research gives voice to the marginalised in the academy. Providing rich and interesting coverage of the approaches to the field of storying research from Aboriginal and white Australian perspectives, this text seeks to enable a profound understanding of the significance of stories and storying. This book will prove valuable for scholars, students and practitioners who seek to develop alternate and creative contributions to the production of knowledge.